Implementasi PERMA No. 2 Tahun 2015 di Pengadilan Negeri Yogyakarta - Bambang Sutiyoso; Ayu Atika Dewi; Fuadi Isnawan (Jurnal Hukum IUS QUIA IUSTUM, 2019)
o overcome the barriers in the dispute settlement in court, the Supreme Court issued a new mechanism for the settlement of civil cases, called as simple civil claims. The procedure mechanism was introduced through the issuance of PERMA No. 2 of 2015 concerning Simple Civil Claim. The researcher in this study intended to observe the implementation of the PERMA of Simple Civil Claim in Yogyakarta DistrictCourt, along with the obstacles. The study was conducted using the empirical juridical research methodand  analytical  descriptive  data  analysis.  From  the research  results,  it  can  be  concluded  that  the implementation of PERMA No. 2 of 2015 concerning Simple Civil Claim in Yogyakarta District Court is still ineffective in practice. This has been determined by various factors such as the rule of law, legal officers, facilities and infrastructure and community. The researcher also found a number of obstaclesfaced in implementing PERMA, some of which were related to the existence of options to choose the procedure  mechanism,  tight  case  qualifications  that  could  be  submitted  through  simple  program procedures and lack of PERMA socialization.